Systematic analysis of non-melanoma skin cancer burden: A comparative study between China and the world from 1990 to 2021 and prediction to 2036 - Su Liang; Tao Sun; Xuesong Jia; Juanmei Cao; Xue Wang (PLoS ONE, 2025)
Objective To compare the characteristics and trends of the non-melanoma skin cancer (NMSC) burden in China and globally, and to provide a basis for the development of effective prevention and control measures in China. Methods Data related to the incidence, death, and disability-adjusted life years (DALYs) of NMSC in China and the world were obtained from the Global Burden of Disease (GBD) 2021 database. The population included in this sutdy were adults aged 20 and above. The Joinpoint regression model was used to estimate the average annual percentage of change (AAPC) to reflect the time trend. Bayesian age-period-cohort model was constructed for prediction, and the coefficient of determination R² was used to reflect the fitting degree of the model. Results From 1990 to 2021, the age-standardized incidence rate, mortality rate and DALYs rate of NMSC in China increased by 707.31%, 16.00% and 10.04%, respectively, all higher than the global level. And the corresponding upward trends were also more obvious, with AAPC of 6.71% (95%: 6.01% − 7.18%), 0.46% (95%: 0.40% − 0.52%) and 0.28% (95%: 0.22% − 0.34%), respectively. The incidence rate and its AAPC of NMSC were higher in men than in women. Moreover, the mortality rate and DALYs rate were also higher in men, but the growth rate was faster in women. The high incidence rate, mortality rate, and DALYs rate of NMSC all occurred in the higher age groups. The age-standardized incidence rates of NMSC in China and globally were predicted to continue to rise over the next 15 years, while the age-standardized mortality rates will decline. Conclusion The burden of NMSC in China remained serious, especially in the context of an increasingly aging population. Relevant authorities should continue to develop and optimize preventive and control measures, especially for men, and adopt targeted measures to reduce the burden of NMSC significantly.